Facilitating peer-led group research through virtual collaboration spaces: an exploratory research study - Richard Walker; Setareh Chong; James Chong (Association for Learning Technology, 2021)
Peer-led group learning is a variation of collaborative learning and is based on 'small groups of students meeting regularly with a peer - one who has additional expertise in the subject matter - to work on problems collaboratively' (Pazos, Micari, and Light 2010). In this study, we explored how a Slack team environment could be used in a blended course design to support students working remotely on individual research projects, helping them in collaborative trouble-shooting and problem-solving activities with their 'near peer'. We drew on lessons learned from an initial trial (2017-2018 cohort) to inform a revised peer-led research design (2018-2019 cohort).Our findings demonstrate the potential of collaborative platforms such as Slack to support near-peer learning, providing distinct channels for questioning, ideas sharing and agile problem-solving support in response to individual queries. The peer-led support contributed to high levels of engagement with the project work and deeper learning, helping less confident students to learn from group members and achieve positive outcomes in their own project work. We discuss the necessary conditions for effective peer-led learning to take place within a virtual space - identifying the clear communication of instructional roles, socialisation of students and responsiveness of near peers as factors influencing the adoption of the targeted learning methods - which we addressed in our revised peer-led design.